Origem e distribuição dos nervos do plexo lombosacral da pelve e coxa em avestruz (Struthio camelus) - Honorato, Angelita das Graças de Oliveira (2017)
The origin and distribution of the lumbosacral plexus (Struthio camelus) nerves were studied in 30 male and female ostriches, approximately 30 days old. Their arterial contingents were marked with stained Neoprene Latex ¨450¨ at 50% and fixed in 10% formaldehyde. The opening of the coelomic cavity was performed by means of dissections to identify the origins of the lumbar plexus nerves, it emerged from the second to the fifth, and from the sacral, from the fifth to the tenth, nerve-sacral nerve, in the cranial and mean regions of the sinsacro. The lumbar plexus emitted the nerves: cranial, femoral and obturatorial coxal, and the sacral plexus the sciatic nerve, the caudal coxal and branches that emerged straight from the plexus, branching into the iliotibial cranial and lateral muscles (pre-acetabular, acetabular and acetabular) ; Iliofibular, ambiens, cranial, middle and caudal iliotrocantérico; External, medial and internal femorotibial; Lateral and medial crural flexors; Caudiliofemoral, caudofemoral and iliofemoral parts (internal and external part); Ischiofemoral; Pubischiofemoral; Medial and lateral obturator, located in the region of the pelvis and thigh. For both plexuses there was the contribution of the furcal nerve, which arose from the fifth sinusal spinal nerve. However, anatomical data on the ostrich are rare and necessary because of the increased demand for consumption of the products and by-products of this animal. The identification of the origin of the lumbosacral plexus evidenced in the sinusal spinal nerves and its ramification in the muscles of the pelvis and thigh of the ostrich (Struthio camelus), there is a great contribution to the bibliographic anatomical collection on this animal.